The Effect of the Foreign Political Strategy of the Republic of Uzbekistan on Domestic Political Processes (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This is it in the article Uzbekistan Republic of external political strategy and his country internal political processes effect seeing will be released . Uzbekistan to independence from what he achieved after international on the field position strengthening in order to done being increased external politics country inside economic, social and political to reforms effect is showing . In particular , diplomatic communications , investments attraction to do and external political cooperation internal stability and reforms done increase for main factors is happening Also in the article of Uzbekistan international organizations with cooperation , geopolitical factors and regional to safety directed external political directions internal political to the environment effect analysis will be done.